2009
DOI: 10.1158/1078-0432.ccr-09-0418
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Immune Recovery and Graft-versus-Host Disease–like Engraftment Syndrome following Adoptive Transfer of Costimulated Autologous T Cells

Abstract: Purpose: Previously, we showed that adoptive transfer of in vivo vaccine-primed and ex vivo (anti-CD3/anti-CD28) costimulated autologous T cells (ex-T) at day +12 after transplant increased CD4 and CD8 T-cell counts at day +42 and augmented vaccine-specific immune responses in patients with myeloma. Here, we investigated the safety and kinetics of T-cell recovery after infusing ex-Tat day +2 after transplant. Experimental Design: In this phase I/II two-arm clinical trial, 50 patients with myeloma received auto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 47 publications
3
68
0
Order By: Relevance
“…[53][54][55] However, accumulating evidence has demonstrated that prolonged in vitro expansion of T cells can cause a progressive loss of replicative capacity and functional exhaustion limiting their in vivo antitumor efficacy. 19,56 To limit the detrimental impact of prolonged in vitro culture, we used a time-constrained exposure to anti-CD3/anti-CD28 to BLOOD, 27 AUGUST 2009 ⅐ VOLUME 114, NUMBER 9…”
Section: Discussionmentioning
confidence: 99%
“…[53][54][55] However, accumulating evidence has demonstrated that prolonged in vitro expansion of T cells can cause a progressive loss of replicative capacity and functional exhaustion limiting their in vivo antitumor efficacy. 19,56 To limit the detrimental impact of prolonged in vitro culture, we used a time-constrained exposure to anti-CD3/anti-CD28 to BLOOD, 27 AUGUST 2009 ⅐ VOLUME 114, NUMBER 9…”
Section: Discussionmentioning
confidence: 99%
“…The apparent difference in CD8 effector memory populations between the primed group and the nonprimed group is not significant and is due to 3 outliers with engraftment syndrome. 30 Therefore, there were no differences in T-cell subsets between the 2 arms.…”
Section: B-cell and T-cell Recovery Kineticsmentioning
confidence: 92%
“…The cells were depleted of monocytes and cryopreserved. The T-cell manufacturing process has been described previously 30 and consisted of CD3 and CD28 bead-based stimulation. All infused T-cell products were required to meet safety and release criteria specified by the Food and Drug Administration before infusion.…”
Section: T-cell Infusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] It has been reported that the day of adoptive T-cell transfers in relation to preconditioning regimens is critical as T cells given at day two after stem cell transplantation show superior persistence as compared to those given in later days. 14 Until recently, development of this personalised T-cell-based therapy was limited due to the lack of gene transfer techniques and efficient T-cell culture systems. Therefore, previous clinical applications with T cells expressing CAR showed modest clinical activities, as these engineered T cells demonstrated a limited expansion in vivo and rapidly disappeared from circulation.…”
mentioning
confidence: 99%